Web-scraping the JDDM database: citations, reads and downloads - Fischer, Andreas; Holt, Daniel; Funke, Joachim (Journal of dynamic decision making, 2018)
The Journal of Dynamic Decision Making launched its fourth volume by the end of 2018. In previous editorials we reflected on the definition of Dynamic Decision Making, on the journals’s content and on related research topics. Today, we want to take the opportunity of writing our fourth editorial to reflect on the citations, reads, and downloads of papers published in the Journal of Dynamic Decision Making, given that four years have passed since we started publishing.